A Multiagent Alphavirus DNA Vaccine Delivered by Intramuscular Electroporation Elicits Robust and Durable Virus-Specific Immune Responses in Mice and Rabbits and Completely Protects Mice against Lethal Venezuelan, Western, and Eastern Equine Encephalitis Virus Aerosol Challenges. (3rd June 2018) - Dupuy, Lesley C.; Richards, Michelle J.; Livingston, Brian D.; Hannaman, Drew; Schmaljohn, Connie S.
Abstract : There remains a need for vaccines that can safely and effectively protect against the biological threat agents Venezuelan (VEEV), western (WEEV), and eastern (EEEV) equine encephalitis virus. Previously, we demonstrated that a VEEV DNA vaccine that was optimized for increased antigen expression and delivered by intramuscular (IM) electroporation (EP) elicited robust and durable virus-specific antibody responses in multiple animal species and provided complete protection against VEEV aerosol challenge in mice and nonhuman primates. Here, we performed a comparative evaluation of the immunogenicity and protective efficacy of individual optimized VEEV, WEEV, and EEEV DNA vaccines with that of a 1 : 1 : 1 mixture of these vaccines, which we have termed the 3-EEV DNA vaccine, when delivered by IM EP. The individual DNA vaccines and the 3-EEV DNA vaccine elicited robust and durable virus-specific antibody responses in mice and rabbits and completely protected mice from homologous VEEV, WEEV, and EEEV aerosol challenges. Taken together, the results from these studies demonstrate that the individual VEEV, WEEV, and EEEV DNA vaccines and the 3-EEV DNA vaccine delivered by IM EP provide an effective means of eliciting protection against lethal encephalitic alphavirus infections in a murine model and represent viable next-generation vaccine candidates that warrant further development.